A guide for microscopic description of fossil stromatolites - Evelyn Aparecida Mecenero Sanchez; Guilherme Raffaeli Romero; Flavia Callefo; Alexandre Ribeiro Cardoso; Thomas Rich Fairchild (Brazilian Journal of Geology, 2023)
Abstract Stromatolites are laminated biosedimentary structures of great importance for paleobiological, paleoecological, and paleoenvironmental analyses, mainly in Precambrian rocks. Their value is related to the glimpse of past life recorded in their lamination, fabric, and, eventually, due to the preservation of organic matter, including microfossils, and because their deposition is directly influenced by environmental conditions. Although stromatolites are widely described in microscopic scale, there is a lack of standardization of their nomenclature, precluding better paleoenvironmental and paleobiological interpretations. In this study, we propose a guide for the microscopic analysis of fossil stromatolites and, possibly, thrombolites, and provide a review of specialized literature and the bibliometric context of main terms. The goal is to contribute to the improvement of their application through systematization of microscopic data, in the face of novel paleoecological and paleobiological approaches and for astrobiological prospection for microbialites in therock record of Mars.